Post Pandemic Business Sustainability Performance on Indonesian Stock Exchange Listed Companies - M. Mulyono (Australasian Accounting, Business and Finance Journal, 2024)
This study aims to examine the effect of the pandemic on the performance of business sustainability implementation related to ESG (Environmental, Social, and Government) in companies listed on ESG-based stock indices on the Indonesia Stock Exchange. ESG-based stock indices are the SRI-KEHATI index, ESG Leaders index, ESG Sector Leader index, ESG Quality 45 index, and IDX LQ45 Low Carbon Leaders Index. ESG score data is obtained from the S&P Global website. There are 31 companies that are listed on the ESG-based index with available ESG score data. The data analysis used in this study is the Wilcoxon Signed-Rank Test and Mann-Whitney Test. The study concludes that the Covid-19 pandemic has positively and significantly affected the company's ESG performance. In the Environmental component, the conclusion is that there is no difference between the performance of the company and its industry. In the Social component, there is a difference between the performance of the company and its industry. In the Governance component, the conclusion is that there is a difference between the performance of the company and its industry. Furthermore, the Social component has a significantly higher average when compared to the assessment of the Social component of the industry. During the pandemic, the company carried out social actions to reduce the impact of the pandemic on the community; the pandemic made the company more sensitive to the condition of the surrounding community. This research provides a view of businesses that are trying to survive during the pandemic by focusing on business sustainability and the community.
Keywords: Business sustainability; Environment; ESG score; Government; Social